Legal Basis and Problems Regarding the Application of a Higher Tax Rate on State Natural Resources - Montvidas, Martynas (Teisė, 2023)
This Article in the context of common rules of liability for infringements of tax laws discloses the legal regulation establishing a higher tax rate on State natural resources and problems related to its application in Case Law.